The association of visual impairments of elite soccer players with concussion and sports injuries: A prospective cohort study - Hassanmirzaei, B.; Fahimipour, F.; Haratian, Z.; Moghadam, N. (Asian Journal of Sports Medicine, 2021)
Background: Visual skills play a pivotal role in athletic performance. However, in a professional setting, visual assessment is limited to a brief examination of visual acuity by the Snellen chart. This is while visual skills in sport comprise several other components. Objectives: This study aimed to evaluate the potential relationship between visual skills and sports injuries in professional soccer players. Methods: Through a prospective cohort study between September 2017 and October 2018, professional soccer league players were recruited for a complete eye examination including visual acuity, field of vision, and color discrimination as pre-competition examination. Any possible relationship between an abnormal eye finding and sports injury during the upcoming season was investigated. Results: A total of 386 male soccer players in 4 different playing positions were recruited from 16 league teams. Myopia, visual field defects, and green/blue/red color blindness were the most common visual impairments. Overall, there was no significant relationship between abnormal visual skills and the incidence of low back and upper extremity injuries among soccer players. However, a logistic regression model showed that the odds of quadriceps injury is 1.92 times higher (P-value: 0.005) for one diopter increase in both eyes' sum of refractive error. There is also an increased risk of concussion in players who have visual field defects (P-value < 0.005). Conclusions: Visual field defects can put soccer players at a higher risk for concussion. Moreover, uncorrected refractive eye errors will increase the incidence of lower limb injuries, mostly quadriceps injuries.